Novel sustainable synthesis of dyes for clean dyeing of wool and cotton fibres in supercritical carbon dioxide. (20th October 2018) - Luo, Xujun; White, Jonathan; Thompson, Richard; Rayner, Christopher; Kulik, Balazs; Kazlauciunas, Algy; He, Weidong; Lin, Long
Abstract: A new synthetic route was developed to create an azo-based reactive disperse dye containing the vinyl sulphonyl reactive group. This dye was used to colour wool and cotton fibres using scCO2 as the dyeing medium. The optimum dyeing process was carried out with water pre-treatment at 90 °C and 140 bar during a 60 min dyeing time. Under optimal conditions, which are relatively moderate for supercritical dyeing processes, the dyed wool fabrics produced uniform dyeings with high colour strength and fastness properties. These wool dyeings provided good colour strength and fixation properties (fixation of 99.4%). Cotton also showed good colour strength results. Crucially, the process did not produce any dyeing effluent. Furthermore, there is a potential to modify a wide scope of disperse dyes using the thiol group via this synthetic method without the need for further purification. Graphical abstract: Image 1